The Impact of Online Games on Learning Motivation of Elementary School Students: Dampak Game Online terhadap Motivasi Belajar Siswa Sekolah Dasar - Adhzani, Febriany Nadilah; Tirtoni , Feri (Indonesian Journal of Education Methods Development, 2023)
This quantitative study aimed to investigate the influence of online games on the learning motivation of elementary school students at SDN Kandangan. The research involved 41 upper-class students in grade 5 as the sample, and data were collected through questionnaires and interviews. The analysis revealed that students addicted to online games experienced a decline in their learning motivation. Teachers and guardians also acknowledged that excessive online gaming, exceeding 3-4 hours a day, led to reduced enthusiasm and motivation for academic learning. Moreover, students addicted to online games faced difficulties in achieving academic success. The research concluded that online games significantly affected the learning motivation of elementary school students. To address this issue, the role of teachers and parents in supervising and educating students about the negative impacts of excessive online gaming is crucial. Highlight: The research aimed to determine the impact of online games on the learning motivation of elementary school students at SDN Kandangan, using a descriptive quantitative research method with 41 upper-class students as the sample. Findings revealed that students addicted to online games experienced a decline in their learning motivation, affecting their enthusiasm and academic achievements. The study emphasizes the crucial role of teachers and parents in supervising and educating students about the negative impacts of excessive online gaming to address the issue of online game addiction and its influence on learning motivation. Keyword: Online Games, Learning Motivation, Elementary School Students, Addiction, Academic Achievements